Pay to play: Understanding gamer’s motivation through semantic analysis - Teh, Phoey Lee *; Irina, Pak * (2021)
Understanding what motivates a gamer to pay to play a game could enhance the gaming industry. One of the ways to understand game players experiences is through exploration via their text communication. This study explores text communication posted on the Steam digital distribution platform on paid-play games. A total of 7255 gamer text communicated were collected and analysed. Reviews from the past pinpointed that elements such as social influence, entertaining features, graphic design, music, and soundtrack used in the game could influence the game playing experience. To study those, we use mix-method (qualitative and quantitative) methods to analyse the data. We invite three human coders to categorise statements associating with its elements and aspects. Next, with the aid of Wmatrix, a semantic analysis system, we tabulate and elaborate the emotion words associating with the gameplay elements. The result shows that the positive feeling of love and joy highly encourages the gamer’s overall game playing experience. Elements such as the storyline, design of the Avatar and the entertaining features are the primary motivation of the gameplay.